The pan-plastome of Prunus mume: insights into Prunus diversity, phylogeny, and domestication history - Wang, Jie; Kan, Junhu; Wang, Jie; Yan, Xinlin; Li, Yi; Soe, Thida; Tembrock, Luke R.; Xing, Guoming; Li, Sen; Wu, Zhiqiang; Jia, Minlong (Frontiers in Plant Science, 2024)
Backgrounds Prunus mume in the Rosaceae and commonly referred to as mei or Chinese plum is widely used as a traditional ornamental flowering plant and fruit tree in China. Although some population and genetic analyses have been conducted for this species, no extensive comparisons of genetic variation from plastomes have yet been investigated. Methods We de novo assembled a total of 322 complete P. mume plastomes in this study and did a series of comparative analyses to better resolve pan-plastomic patterns of P. mume. To determine the phylogeny and domestication history of this species, we reconstructed the phylogenetic tree of Prunus genus, and resolved the population structure of P. mume. We also examined the nucleotide variation of P. mume to find potential DNA barcodes. Results The assembled plastomes exhibited a typical quadripartite structure and ranged from 157,871 bp to 158,213 bp in total size with a GC content ranging from 36.73 to 36.75%. A total of 112 unique genes were identified. Single nucleotide variants (SNVs) were the most common variants found among the plastomes, followed by nucleotide insertions/deletions (InDels), and block substitutions with the intergenic spacer (IGS) regions containing the greatest number of variants. From the pan-plastome data six well-supported genetic clusters were resolved using multiple different population structure analyses. The different cultivars were unevenly distributed among multiple clades. We also reconstructed a phylogeny for multiple species of Prunus to better understand genus level diversity and history from which a complex introgressive relationship between mei and other apricots/plums was resolved. Conclusion This study constructed the pan-plastome of P. mume, which indicated the domestication of P. mume involved multiple genetic origins and possible matrilineal introgression from other species. The phylogenetic analysis in Prunus and the population structure of P. mume provide an important maternal history for Prunus and the groundwork for future studies on intergenomic sequence transfers, cytonuclear incompatibility, and conservation genetics.